The BDNF Val66Met gene polymorphism is associated with increased alexithymic and anticipatory anxiety in patients with panic disorder. Issue 4 (21st April 2019) - Zou, Zhili; Qiu, Jian; Huang, Yulan; Wang, Jinyu; Min, Wenjiao; Zhou, Bo
ABSTRACT: A large body of evidence indicates that patients with panic disorder(PD) report more obvious alexithymia, and previous studies suggest genetic factors may be play an important role in alexithymia. This study aims to examine the association between the Brain-derived neurotrophic factor (BDNF) Val66Met polymorphism and alexithymia, and then to evaluate the association of the BDNFVal66Met polymorphism with PD risk. 223 patients with PD and 218 healthy controls were enrolled in the study. The Toronto Alexithymia Scale (TAS-20), and Panic Disorder Severity Scale (PDSS) were administered to all subjects. And genotyping of the BDNF Val 66Met polymorphism was evaluated. Our results showed that both PD patients and normal controls with the BDNF Met/Met genotype had significantly higher total and difficulty describing feelings(DDF) subdimension scores on the TAS-20 than those with the Val/Val genotype.The patients with the BDNF Met/Met genotype were more severity of anticipatory anxiety than patients with Val/Val genotype.